Growth and Characterization of Ga2O3 for Power Nanodevices Using Metal Nanoparticle Catalysts - Badriyah Alhalaili; Antony Joseph; Latifa Al-Hajji; Naser M. Ali; Sowmya Dean; Ahmad A. Al-Duweesh (Nanomaterials)
A simple and inexpensive thermal oxidation process is used to grow β-Ga2O3 oxide (β-Ga2O3) thin films/nanorods on a c-plane (0001) sapphire substrate using Ag/Au catalysts. The effect of these catalysts on the growth mechanism of Ga2O3 was studied by different characterization techniques, including X-ray diffraction analysis (XRD), Scanning Electron Microscopy (SEM), and Energy Dispersive X-ray analysis (EDX). The XRD results of the grown Ga2O3 on a sapphire substrate show three sharp diffraction peaks located at 19.31°, 38.70° and 59.38° corresponding to the <semantics><mfenced separators="|"><mover accent="true">2¯</mover>01</mfenced>, <mfenced separators="|"><mover accent="true">4¯</mover>02</mfenced></semantics> and <semantics><mfenced separators="|"><mover accent="true">6¯</mover>03</mfenced></semantics> planes of β-Ga2O3. Field Emission Scanning Electron Microscope (FESEM) analysis showed the formation of longer and denser Ga2O3 nanowires at higher temperatures, especially in the presence of silver nanoparticles as catalysts.